EfeEfektivitas Pengawasan Pangan Fortifikasi oleh Badan POM sebagai Intervensi Penurunan Stunting di Provinsi Lampungktivitas Pengawasan Pangan Fortifikasi Oleh Badan POM Sebagai Intervensi Penurunan Stunting Di Propinsi Lampung - Yulia Rahmawati (Badan Pengawas Obat dan Makanan, 2022)
Stunting is a national development problem because stunting has an impact on the decline in the quality of Indonesian people. Efforts to accelerate stunting reduction include specific nutrition and sensitive nutrition interventions. Consumption of fortified food is part of a sensitive nutrition intervention. This paper aims to see the effectiveness of fortified food supervision carried out by the Indonesian FDA Provincial Office in Bandar Lampung. The methodology used is to analyze the data obtained from the results of the supervision of the Indonesian FDA Provincial Office in Bandar Lampung in 2018-2021 with the stages of collecting test data for samples of fortified food products in 2018-2021 for consumption of iodized salt and wheat flour and cooking palm oil; calculate the percentage comparison of the test results for fortified food product samples that meet the requirements (MS) with those that do not meet the requirements (TMS); analyze the data obtained by looking at the increase or decrease in the test results that meet the requirements (MS) with those that do not meet the requirements (TMS). The testing results for fortified food products such as iodized salt, wheat flour, and cooking oil have increased for products with MS every year. A product is said to meet the requirements if it meets the standards and requirements for safety, efficacy/benefits, and product quality. This result indicates the success of the supervision carried out by the Indonesian FDA Provincial Office in Bandar Lampung. Supervising the Indonesian FDA's fortification food as a stunting intervention in Lampung Province is effective.